Dinâmica de herbicidas em palha de cana-de-açúcar - Araldi, Rosilaine; Velini, Edivaldo Domingues [UNESP]; Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Tropaldi, Leandro [UNESP]; Silva, Ilca Puertas de Freitas e [UNESP]; Carbonari, Caio Antonio [UNESP] (FapUNIFESP (SciELO), 2015)
The process of mechanical harvesting of sugarcane generates a large deposition of straw on the soil surface, providing a coverage that several studies have found important for reducing the weed population. Although such coverage reduces weed infestations, additional management, including chemical control, is still needed. Thus, this study aimed to evaluate the leaching of atrazine, pendimethalin, metribuzin, clomazone, diuron and hexazinone in sugarcane straw. The experiment was conducted at the School of Agronomic Engineering at UNESP (Universidade Estadual Paulista) - Botucatu/SP. The sugarcane straw was collected in the field, cut and placed in quantities of 10t ha-1 in the capsules used as experimental units. The experimental design was completely randomized, using six herbicide treatments and four replications. Within 24 hours after the herbicides were applied in capsules with straw, five different rainfalls (5, 10, 20, 50 and 100mm) were simulated. The leached water was collected for chromatographic analysis. The herbicide percentages that crossed the straw layer were statistically correlated with the rainfall amount by the Mitscherlich model that compares the facility of herbicide removal from sugarcane straw. In summary, pendimethalin did not present quantified transposition of the product by sugarcane straw even with a rain simulation of 100 mm. Furthermore, two different profiles of facility to transpose the herbicides in straw were found: one for metribuzin and hexazinone that crossed quickly through the straw layer and another for atrazine, diuron and clomazone that required more rainfall to be leached from coverage to the soil according to the maximum removable amount of each herbicide.
Performance of herbicides in sugarcane straw
Keywords: Atrazine; Clomazone; Diuron; Hexazinone; Metribuzin; Pendimethalin